2017
DOI: 10.1111/jocd.12460
|View full text |Cite
|
Sign up to set email alerts
|

Skin care and cosmeceuticals: Attitudes and trends among trainees and educators

Abstract: Skin care and cosmeceutical recommendations are often discussed in dermatology visits. Dermatology residents feel that education on these products should be a part of their residency training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The demand for new skincare ingredients, especially based on natural products, strongly increased during the last few decades 1,2 . Plant bioactive metabolites are most of the time free from harmful side effects, hence, great importance is given to the research of naturally occurring anti-ageing agents.…”
Section: Introductionmentioning
confidence: 99%
“…The demand for new skincare ingredients, especially based on natural products, strongly increased during the last few decades 1,2 . Plant bioactive metabolites are most of the time free from harmful side effects, hence, great importance is given to the research of naturally occurring anti-ageing agents.…”
Section: Introductionmentioning
confidence: 99%
“…The World Economic Forum presents the constantly changing 4th Industrial Revolution [1] as the connection structure shown in Figure 1.The 4th Industrial Revolution is the combination of an offline world in real life established by the 1st and 2nd Industrial Revolutions and a virtual online world established based on the 3rd Industrial Revolution which is a digital revolution.The 1st Industrial Revolution is the hydraulic power and vapor-based manufacturing revolution based on mechanization and the 2nd Industrial Revolution is the mass production basedon electricalenergy. The 3rd Industrial Revolution is the information technology revolution of computer and Internet.Figure 2 below shows a change in the industrial revolution [2].…”
Section: Development Of the 4 Th Industrymentioning
confidence: 99%
“…Nowadays, the public has become more aware of the importance of skin care and professionals are often consulted to obtain recommendations and make better selections of appropriate products. A cross-sectional survey of dermatology residents and der-matology faculty members performed in 2015 found that dermatology residents feel that education on these products should be included in residency training [210]. Recognition by the medical community of the variety and functionality of cosmeceutical products available on the market would bring more attention to the industry and, if the claims purported by the products are substantiated by tests like the ones mentioned above, this could lead to the validation of cosmeceuticals as a separate category of products from cosmetics.…”
Section: Perspectives In Cosmeceutical Developmentmentioning
confidence: 99%